Corneal Astigmatism among first year undergraduate students of UiTM Selangor, Puncak Alam Campus / Nurulwahida Jasman - Jasman, Nurulwahida (2016)
Background: Previous studies stated that 13 % of the refractive error of human eye comes from astigmatism and the origin of the astigmatism was mostly from the cornea and is known as corneal astigmatism. Based on previous studies, there were low amount of astigmatism reported among adults, the most commonly was WTR astigmatism. However, prevalence of astigmatism was higher among Asian as compared to Caucasian subjects. Previous studies reported that there were association between corneal astigmatism and refractive astigmatism. However, limited study done in Malaysia on corneal astigmatism especially among young Malay adults. Purpose: This study aims to identify corneal astigmatism including its direction and its relationship with refractive astigmatism among first year undergraduate students of UiTM Selangor, Puncak Alam Campus. Method: First year university students of UiTM Selangor, Puncak Alam campus were invited to participate in the study. In this study, corneal astigmatism was measured by using Nidek Magellan Mapper SN MM 2062 2004/5 with the following standard optometric procedure; A drop of saline solution was instilled into the inferior fornix in order to maintain adequate tears. Then, proper fixation was ensured as the subjects were asked to see the central green light in the instrument. Three consecutive readings were taken and average readings were recorded for each eye. Result: The mean corneal astigmatism of the first year undergraduate students of UiTM Selangor, Puncak Alam campus for the right and left eyes were 1.01 ± 0.58DC, and 1.07 ± 0.63DC respectively. Among them, 46% was found to have astigmatism greater than 1.00DC. The direction of corneal astigmatism was predominantly with-the-rule (WTR) astigmatism, (79%). Besides, there was good correlation between corneal astigmatism and refractive astigmatism as r = 0.75 with p=0.0005. Conclusion: Forty six percent of the first year students has astigmatism more than 1.00DC and 79% was WTR astigmatism. The high percentage of astigmatism had importance implications for future service planning as it may be associated with lazy eye and poor quality of life.